(untitled) (CIPEEX, 2025)
Occupational accidents are complex and influenced by multiple factors, including inadequate working conditions and the incorrect use of Personal Protective Equipment (PPE). This study aimed to evaluate the epidemiological profile of notified cases of occupational accidents with exposure to biological material in two health regions of the state of Goiás. The research used an integrative review of Brazilian literature to synthesize the results of primary research between 2019 and 2024, focusing on healthcare professionals who suffered occupational accidents with exposure to biological materials. The results show that the most common accidents occur among nursing technicians, predominantly female, representing 70.7% of the analyzed cases. The sociodemographic analysis evidenced the female majority and highlighted the importance of implementing specific preventive measures that consider the socioeconomic and cultural factors of this professional class. Data from FIOCRUZ show an increase in notifications of accidents involving nursing technicians in recent years, emphasizing the relevance of discussing and improving safety in the work environment for these professionals. The importance of understanding the causes of these accidents to reduce their frequency was highlighted. The implementation of educational initiatives focused on worker protection and the correct use of PPE is recommended, aiming to contribute to the creation of safer and healthier work environments for healthcare professionals.